CONNECTION WITH SELF-EFFICACY ON PSYCHOLOGICAL PRESSURE OF CORRECTIONAL OFFICERS IN CLASS I COMMUNITY INSTITUTIONS TANGERANG - Sujono, Salman Al Farizy; Aulia, Qisthina; Tando, Cahyoko Edi (Jurnal Kajian Pendidikan dan Psikologi, 2023)
The aim of this research is to find out whether there is a relationship between self-efficacy and psychological distress, especially among officers at the Class I Prison in Tangerang. This is quantitative research using a simple linear regression method, and the research sample consists of 132 respondents. The technique used is non-probability sampling. Research data was taken using the General Self-Efficacy Scale and the DASS 21 questionnaire. This research produced an R value of 0.189 and an R square of 0.036, a significance level of p 0.030 (<0.005), and a regression line equation of Y = 18.090+ 0.368X. The results of the research show a significant negative relationship between the self-efficacy variable and the psychological distress variable, meaning that the higher the self-efficacy the officers have, the lower the psychological distress they experience. The advice given by researchers is that there needs to be support for the development of strong self-efficacy through training, self-development, and appropriate support that can help reduce the level of psychological distress that may arise when officers face obstacles in achieving goals.